Study of processability of poly(vinyl chloride): Effects of acrylic and chlorinated polyethylene impact modifiers, oil palm empty fruit bunch fiber, and mixing temperature - Bakar, Aznizam Abu; Hassan, Azman; Yusof, Ahmad Fuad Mohd (Wiley InterScience, 2008)
The influence of acrylic impact modifier, chlorinated polyethylene (CPE) impact modifier, oil palm empty fruit bunch (OPEFB) fiber, and mixing temperature on the processability of poly(vinyl chloride) (PVC) compounds was investigated. The acrylic impact modifier was the most efficient additive in reducing the fusion time of the PVC, followed by the OPEFB fiber and the CPE impact modifier, whereas OPEFB was the most efficient in decreasing the melt viscosity of the compounds, followed by CPE and acrylic. A PVC compound containing 9 phr of CPE and 40 phr of OPEFB had high values of fusion time and end torque. The fusion time and melt viscosity of all of the PVC compounds decreased with increasing mixing temperature